In-silico identification of bacterial key-genes directly or indirectly associated with the development and progression of colorectal cancer for exploring anti-bacterial agents - Nibas Kumar Pal; Md. Kaderi Kibria; Tasfia Noor; Md. Feroj Ahmed; Md. Shariful Islam; Md. Foysal Ahmed; Md. Abdul Latif; Mohammad Ali; Md. Al Noman; Dipto Kundu; Ovi Sharma; Md. Nurul Haque Mollah (PLoS ONE, 2026)
Colorectal cancer (CRC), which includes malignancies of the colon and rectum, constitutes a major global health challenge. Though there are several drugs that targets CRC-related genes/proteins, but their performance is not yet reach to the satisfactory level. Moreover, their effectiveness gradually decreases over time with long-term use, a phenomenon known as drug resistance. Therefore, it is required to explore new alternative candidate drugs against CRC. Several studies recommended CRC-related dysregulated host-genes guided candidate drugs. However, microbiome guided drug discovery particularly targeting bacterial key genes (bKGs) within CRC-associated gut microbiota remains very limited. This study aims to identify bKGs as antibacterial targets within CRC-associated bacterial taxa for exploring anti-bacterial agents. At first, we analysed a 16S rRNA-seq profile dataset that contained 24 CRC and 50 healthy samples, where beta diversity analysis results showed significant differences in bacterial compositions between CRC and HC groups. Differential abundance analysis with threshold values at |log 2 FC| > 1.0 and adjusted p -value < 0.05 identified 42 significantly altered bacterial taxa of which Bacteroides fragilis, Bacteroides ovatus, Bacteroides uniformis, and Flavonifractor plautii were prioritized based on effect size and published literature reporting their association with CRC. Further, an integrative subtractive genomics and protein-protein interaction (PPI) network analyses was used to identify top-ranked 10 essential bKGs ( ribD, ribBA, murA, alr, hisI, hisE, hisD, hisG, hisH, and hisB ) from these four CRC-associated bacterial taxa as putative antibacterial targets. Finally, three candidate drug molecules (Sulfasalazine, Aminoglutethimide, and Tipiracil) were recommended as the preliminary bKGs-guided candidate anti-bacterial agents for CRC through molecular docking and ADME/T analyses. Further experimental and clinical validation is required to establish these compounds as the effective drugs targeting the bKGs for CRC. Thus, these findings may provide insights for developing innovative anti-bacterial treatment approach relevant to CRC.